Scope for export-led growth in a large emerging economy: Is India learning by exporting? - Saleh S. Tabrizy; Natalia Trofimenko (Kiel Institute for the World Economy (IfW), 2010)
The ongoing debate of the literature on learning-by-exporting is whether the conspicuously stellar performance of exporters relative to non-exporters can be, at least partially, attributed to the horizonwidening interaction with foreign consumers and learning of cost-efficient and quality enhancing production methods, or whether all of the differential is due to the self-selection of best firms into exporting. This study uses data from the 1998-2008 Prowess Database to examine how firm-level productivity paths differ between firms with varying degrees of exposure to international trade in India, the country to rank third among the most dominant economies by the year 2050. Having used Levinsohn-Petrin measure of total factor productivity and a proxy for labor productivity, we find significant ex-ante differences in productivity between exporters and non-exporters and no difference in the ex-post productivity gains. These findings suggest that even in a large emerging economy with strong absorptive capacity and a significant catch-up potential, learning-by-exporting effects are nonexistent. Rather, self-selection of more productive firms into exporting explains the productivity differential between exporters and non-exporters.
Keywords: D21; F10; L60; 330; Trade; total factor productivity; exports; export-led growth; learning by exporting; Exportinduziertes Wachstum; Exportindustrie; Lernprozess; Produktivität; Unternehmensentwicklung; Landesgröße; Schätzung; Indien